2019
DOI: 10.21276/aan.2018.3.2.5
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Emergence Characteristics, Intraoperative Haemodynamics and Intraoperative Brain Relaxation between Isoflurane and Desflurane in Patients Undergoing Craniotomy for Supratentorial Lesions.

Abstract: Background: Desflurane had increased anaesthetic armamentarium for maintenance of general anesthesia in neurosurgical cases. Few studies have compared isoflurane and desflurane for patients undergoing elective supratentorial craniotomy. Aims: The aim of this study is to compare emergence characteristics, intraoperative haemodynamic and intraoperative brain relaxation between isoflurane and desflurane in patients undergoing craniotomy for supratentorial lesions. Settings and Design: Prospective randomized and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…13,[23][24][25][26] A study conducted by Chahar et al,27 found that both desflurane and isoflurane can be used in patients undergoing supratentorial craniotomy with desflurane having added advantage of faster post-operative recovery and emergence characteristics. Although both desflurane and isoflurane had comparable brain relaxation grades, 23 patients in desflurane group had Grade 1 brain swelling in comparison to 18 patients in isoflurane group (P=0.35).…”
mentioning
confidence: 99%
“…13,[23][24][25][26] A study conducted by Chahar et al,27 found that both desflurane and isoflurane can be used in patients undergoing supratentorial craniotomy with desflurane having added advantage of faster post-operative recovery and emergence characteristics. Although both desflurane and isoflurane had comparable brain relaxation grades, 23 patients in desflurane group had Grade 1 brain swelling in comparison to 18 patients in isoflurane group (P=0.35).…”
mentioning
confidence: 99%